Pelatihan Analisis Data Kependudukan bagi Kader Kampung Keluarga Berkualitas di Kabupaten Batang Hari - Zulfanetti; Heriberta; Parkhurst, Helen; Mukhzarudfa; Parmadi; Minati, Jurnia (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The purpose of this Community Service (PPM) activity is for Quality Family Village (KKB) cadres to understand, be able to create and analyse population data, starting from data collection, data organisation, descriptive analysis, spatial analysis, identification of population problems, knowing priority problems, developing solutions, program implementation, monitoring and evaluation. The method of service carried out is socialisation through material exposure, lecture method and participatory approach, as well as training on various population data indicators, especially Batang Hari Regency data. The results of PPM activities are that the cadres of the Quality Family Village are very enthusiastic in participating in training activities on the analysis and utilisation of population data for the Population Data House concerned. With activities like this, KKB cadres already understand, are able to analyse, and utilise the available data and present more interesting data with complete information, to solve population problems in the village. The Head of PPKBP3A Office and KKB cadres hope that in the future this kind of activity will be held regularly and continuously, so as to achieve the classification of Rumah DataKu plenary and sustainable KKB.